Pakistan Society of Hepatology Guidelines on the Management of Hepatic Encephalopathy: Guidelines for Managing Hepatic Encephalopathy - Naeem, Muhammad Usman; Malik, Kashif; Fareed, Amna; Kashif, Ramsha; Haider, Ali; Ghilzai, Daud; Ramzan, Hafiza Sobia (Pakistan Journal of Health Sciences, 2024)
Hepatic Encephalopathy (HE) is one of the major complications in patients with liver cirrhosis. Cirrhosis is a significant health burden worldwide, and due to the increasing population and aging, the burden has increased since 1990. The pathogenesis of HE has been explained by different hypotheses, like astrocyte dysfunction, the ammonia hypothesis, and the GABA hypothesis. Hyperammonemia is the most likely cause of MHE. The breakdown of amines, amino acids, and purines by bacteria in the gastrointestinal tract leads to the production of ammonia. Ammonia is converted to urea in the liver by the Krebs-Henseleit cycle. Guidelines are made to help physicians and gastroenterologists diagnose patients at an early stage of hepatic encephalopathy, and a prompt diagnosis can prevent overt hepatic encephalopathy. Since no previous national guidelines regarding PSE are available, the aim here is to create a unifying guideline regarding the treatment of both overt and covert encephalopathy in a cost-effective manner. The management plan given in these guidelines is flexible and can be changed with more authentic data. We recommended that these guidelines provide a valuable source of information regarding HE in the Pakistani population, its current diagnosis, and its treatment. There is a high cost of treatment for liver diseases, and according to the current available data, we must follow the guidelines of PSH.